Emerging Developmental Pathways to ADHD: Possible Path Markers in Early Infancy - Judith G. Auerbach; Naama Atzaba-Poria; Andrea Berger; Rivka Landau (Neural Plasticity)
Sixty-six male infants participating in the Ben-Gurion Infant Development Study of familial risk for attention deficit hyperactivity disorder (ADHD)were assessed at 7 months of age using observational and mother report measures. Risk for ADHD was based on ADHD symptoms in the father. Infants whose fathers had seven or more symptoms formed the ADHD risk group; infants whose fathers had three or less symptoms formed the comparison group. The ADHD risk group significantly differed from the comparison group on measures of interest, anger, and activity level and showed less interest in block play and more anger reactivity but less directed anger in a barrier task. According to mother report, the ADHD risk group had higher levels of activity than the comparison group. Measures of neonatal immaturity and activity were related to behavior at 7 months. The findings suggest that possible developmental pathways to ADHD may be emerging in early infancy.